2020
DOI: 10.1073/pnas.2015672117
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-controlled cross-linking in linker-mediated vitrimers

Abstract: Recently developed linker-mediated vitrimers based on metathesis of dioxaborolanes with various commercially available polymers have shown both good processability and outstanding performance, such as mechanical, thermal, and chemical resistance, suggesting new ways of processing cross-linked polymers in industry, of which the design principle remains unknown [M. Röttger et al., Science 356, 62–65 (2017)]. Here we formulate a theoretical framework to elucidate the phase behavior of the linker-mediated vitrimer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…50 Lei et al, proposed a new simulation framework for predicting phase behavior of vitrimers created by the metathesis reaction of dioxaborolanes where they found that the mechanical properties of the vitrimer in the low-temperature regime are controlled by the concentration of the free linker. 51 Molecular dynamics simulations in conjunction with mode-coupling theory (MCT) have also been used to understand and predict the glass behavior of vitrimeric polymers. 52 More recently, we proposed a simulation methodology that utilizes coarse-grained MD in conjunction with a Monte Carlo (MC) method to capture the associative bond exchange in vitrimers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Lei et al, proposed a new simulation framework for predicting phase behavior of vitrimers created by the metathesis reaction of dioxaborolanes where they found that the mechanical properties of the vitrimer in the low-temperature regime are controlled by the concentration of the free linker. 51 Molecular dynamics simulations in conjunction with mode-coupling theory (MCT) have also been used to understand and predict the glass behavior of vitrimeric polymers. 52 More recently, we proposed a simulation methodology that utilizes coarse-grained MD in conjunction with a Monte Carlo (MC) method to capture the associative bond exchange in vitrimers.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, with the aid of a coarse‐grained model, Ciarella et al, demonstrated that the existence of defects in the model vitrimer facilitates the bond exchange and eventually accelerates stress relaxation in the network 50 . Lei et al, proposed a new simulation framework for predicting phase behavior of vitrimers created by the metathesis reaction of dioxaborolanes where they found that the mechanical properties of the vitrimer in the low‐temperature regime are controlled by the concentration of the free linker 51 . Molecular dynamics simulations in conjunction with mode‐coupling theory (MCT) have also been used to understand and predict the glass behavior of vitrimeric polymers 52 .…”
Section: Introductionmentioning
confidence: 99%
“…S1c). This non-monotonic dependence originates from an entropic effect recently found in linker-mediated vitrimers [34,37,38]. Moreover, the position and height of f P2C can be also tuned by changing the concentration of B and D molecules, i.e., βµ B and βµ D (Fig.…”
Section: Entropy Driven Crosslinkingmentioning
confidence: 80%
“…For the second reaction in Fig. 1a, we double the forward reaction flux to equalize the flux between the two states before and after the reaction [34]. Furthermore, for mimicking the actual topology and reaction dynamics of vitrimers, i.e., the covalent bondexchange dynamics in Fig.…”
Section: Monte Carlomentioning
confidence: 99%
See 1 more Smart Citation